Developing a Tri-N Integrated Project-Based Learning Module to Enhance Primary Students’ Creativity in Indonesian Language Learning - Sari Dewi Prastiwi; Banun Havifah Cahyo Khosiyono; Biya Ebi Praheto; Jamiu Temitope Sulaimon (AL-ISHLAH: Jurnal Pendidikan, 2025)
Developing students’ creativity in primary education is essential for preparing them to face 21st-century challenges. However, Indonesian language instruction in elementary schools often lacks teaching materials that effectively foster creative thinking. This study aims to develop and evaluate a Tri-N integrated project-based learning (PjBL) module—rooted in the Javanese educational philosophy of Niteni (observe), Nirokke (imitate), and Nambahi (develop)—to enhance creativity in Indonesian language learning. The study employed a research and development (RD) approach using the ADDIE model. The module was developed through needs analysis, expert validation, and implementation in two elementary schools. Data were collected via observations, questionnaires, interviews, and documentation. A pretest-posttest design was used to assess the effectiveness of the module, with creativity measured using observation rubrics and N-Gain analysis. The module received high feasibility ratings from experts (100% for teaching materials, 95.71% for content, and 98.97% from practitioners). Creativity scores significantly increased in both trials: from 40.00% to 82.29% (N-Gain = 0.711) in the limited trial and from 40.60% to 83.10% (N-Gain = 0.722) in the wider trial. Teachers and students reported positive experiences with the module's structure, visual appeal, and engagement level. The findings support the Tri-N integrated PjBL module as an effective and culturally grounded innovation for fostering student creativity in language learning. Further research is recommended to explore its scalability across subjects and contexts.